Psalms as Torah : reading biblical song ethically - Wenham, Gordon J. (Grand Rapids, Mich. : Baker Academic, 2012)
The Psalms are the most-read part of the Old Testament, but their importance for ethics has often been overlooked. However, the Psalms offer some of the most potent ethical instruction in the Bible. In this book internationally renowned Old Testament scholar Gordon Wenham examines the source of the Psalms' power, reflects on their main ethical themes, and shows how they function as prayers that change us. --from publisher description
Includes bibliographical references (p. 209-215) and indexes.
Keywords: Bible. -- Criticism, interpretation, etc; Ethics in the Bible